Governmental Lodging and Recreation with The Approach of Tropical Architecture - D. D Harisdani; Zafirah N (International Journal of Architecture and Urbanism, 2021)
Lodging and recreational activity are essential activities for training, often held at office of Pusat Pengembangan, Pemberdayaan Pendidik dan Tenaga Kependidikan (PPPPTK) Medan. Office of Pusat Pengembangan, Pemberdayaan Pendidik dan Tenaga Kependidikan (PPPPTK) Medan has had one building as a homestead, but as time progress, the demand for this homestead increase because of the increased activity in recent years. Therefore, the expansion of the homestead and recreational space design is vital to support the training activities. This homestead and outdoor recreation centre design use the methodology to solve problems using a qualitative approach and a quantitative approach by following the data and analysis of the surrounding environment as well as the established governmental building guidelines. The implementation of tropical architecture in the design makes it able to achieve efficient use of energy and be environmentally friendly. This can be seen in the mass concept, indoor concept, outdoor concept, structural concept, circulation system, and utility system. Also, this design blends with the local value of the surrounding environment by applying local wisdom.